Performance Analysis of Various FACTS Controllers Used for Voltage Stability Improvement in Power System - Singh, Santosh Kumar (INDIAN JOURNAL OF SCIENCE AND TECHNOLOGY, 2023)
Background: In order to maintain a reliable and safe electrical grid, voltage stability is considered as a crucial component of power system. The incorporation of Static Compensator (STATCOM) has been a viable approach in recent times to improve voltage stability and alleviate problems related to voltage instability. Methodology: An extensive investigation of the effects of FACTS devices is included in this article, including STATCOMs, on voltage stability within power systems. Mathematical modelling and simulated Doubly Fed Induction Generator (DFIG) based wind turbine is integrated with IEEE-9 bus in MATLAB2020. Finding: This study employs an advanced modelling and simulation technique to assess the performance of STATCOM in various scenarios, considering different fault conditions and contingencies. Overall work is implemented in MATLAB2020. Simulation results are obtained in the terms of voltage profile, reactive power, wind voltage and active power. The values of the parameters before fault is obtained with a reactive power of -33.44 MVAR and voltage of -0.5586 V. After fault, the reactive power is measured as -85.38 MVAR and Voltage is increased to -0.1766 V. Finally, by using STATCOM, the reactive power is reduced to -30.29 MVAR and Voltage -0.5690 V. Further the obtained results are evaluated and compared with the other approaches. Additionally, the paper investigates the optimal placement of STATCOM at load side to maximise their effectiveness in voltage stability enhancement. Novelty and Application: This study contributes a valuable knowledge to power system operators, planners, and researchers, facilitating the informed decisions for the integration and utilisation of STATCOM technologies to ensure the robustness and reliability of modern electrical grids.
uGDX
Keywords: Doubly Fed Induction Generator (DFIG); Wind Energy; IEEE9 Bus; Static Compensator (STATCOM); Voltage Stability; Reactive Power